Biomorphology Characteristics Of Pineapple Plant. (Texas Journal of Agriculture and Biological Sciences, 2024)
Pineapple is a plant with a soft body, about 1-2 meters in height and width. A pineapple flower is an inflorescence that usually develops from an apical merstem. Produces 50 to 200 individual flowers during flowering. The flower is spiral-shaped and covered with a crown of about 150 short petals. . Pineapple fruit is rich in vitamins A, B1, B6 and C, copper, manganese and potassium.